Rediseño del proceso de otorgamiento de créditos y cobranzas de una empresa comercial maderera ubicada en Lima - Sánchez Quispe, Jhon Jambler (2024)
The study evaluated the impact of the redesign of the credit granting and collection process on the profitability of the Remart company. Using a quantitative approach and a non-experimental design, data were collected through documentary analysis of financial statements and income statements between 2021 and 2022. The results showed that the redesign of the credit granting and collections process has had a positive effect on the company's profitability. Despite a decrease in total assets of S/910 thousand soles and a reduction in equity of S/713 thousand soles, the company managed to increase its net sales by S/1,097 thousand soles, reaching a total of S/314,574 thousand in 2022. Gross profit increased by S/713 thousand, and net income rose to S/10,419.87 thousand soles, compared to S/7,332 thousand in 2021, evidencing an improvement in overall profitability due to the optimization of credit processes.